Design automation and simulation of fixed/reconfigurable finite impulse response filters - Pang, Yuanchen. (2009)
This report is aiming of fulfilling the Bachelor's Degree of Electrical and Electronic engineering in NTU. In this report the ReMB and the DAG fusion techniques are employed and a new design methodology is proposed to reduce the area-time complexity of these two techniques. The Programmable Data Scalar (PDS), newly developed methodology, is to reduce the number of operators in the circuit. The common subexpressions that are identified then eliminated based on a continuously updated reference matrix of common subexpression‟s frequency of occurrences. Judgment based on certain design parameters is then employed to perform the scheduling of operators to control steps. By gathering the compatible operators in the same control steps, more operators can be saved and the bit-length of the applied operators is relatively small to lower the area cost of the design.